STUDI STRATEGI PENINGKATAN DAYA BELI MASYARAKAT DIBEKASI - Fitriani, Efi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2017)
This study aims to determine the basic economic sector in Bekasi and determine the strategy of development of the leading economic sector so that programs and activities and activities can be conducted related to the increase in purchasing power of people. The method used in this research is Located Quotient (LQ) and SWOT analysis. LQ is used to determine the base and non-base sectors whereas the SWOT analysis is used to determine the strategy to be used to increase purchasing power of people. The strategy to increase purchasing power in Bekasi is the development of the leading economic sector with several programs. The program is done to increase employment and income per capita so that the purchasing power of Bekasi also increased. Keywords: Purchasing power, LQ, SWOT